Rocket Drag Prediction Method For Optimizing Design And Flight Performance. - Gunsalam, Henry; Mohd Yusof, lIIyia (2004)

(untitled)
This paper discuses about rocket aerodynamic drag prediction methods for optimization of range. Methods presented in this paper could be used as an initial guideline or a quick reference to approximate aerodynamic drag of a rocket. Parameters associated to a rocket's aerodynamic drag can be established in three Distinctive types: wave drag. skin friction drag and base drag, Details on these drag types generated by the various sections of a rocket's body are explained under various speed conditions.